IT governance mechanisms in higher education - Bianchi, Isaías Scalabrin (2016)
Information technology (IT) has become essential in supporting the growth and sustainability of all types of organizations. Higher education institutions are a special type of organization where technological infrastructure consists of a variety of applications, different platforms, academic systems, cloud applications and heterogeneous technologies. All these technologies for supporting the research, teaching and administrative processes require an effective IT governance framework. The framework of IT governance is composed of structures, processes and relational mechanisms. Each one of these mechanisms has a function and when implemented, should affect the organization positively. The process of identifying the right mechanisms to a specific context is a complex endeavor. This paper looks at the IT governance mechanism that higher education institutions have implemented. We did an extensive literature review making use of databases such as Web of Science, IEEE, SCOPUS, or AIS eLibrary for selecting case studies. We discuss these practices in the context of higher education. To continue this research and improve the IT governance body of knowledge for higher education institutions, future works are pointed out.